Do development projects link smallholders to markets? - Ayako Ebata; Silke Hüttel (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2015)
The objective of this paper is to understand the mechanisms by which development projects facilitate market linkage of smallholder farmers based on panel data from Nicaragua. We find that activities related to entrepreneurial practices have positive and statistically significant effect on commercialization. We also find that increased commercialization is positively correlated with total bean sales income, suggesting a positive indirect effect of the activities. Other activities demonstrate no positive and robust effect on commercialization while direct positive effects on sales income can be observed. This implies that market linkage of smallholder farmers require different sets of intervention tools than traditional farm technical assistance.
Keywords: O13; Q17; Q18; 330; Central America; NGO project; Market linkage; Impact Assessment